2009
DOI: 10.1007/s10900-008-9142-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferences Among Immigrant Hispanic Women for Written Educational Materials Regarding Upper Respiratory Infections

Abstract: The need for culturally appropriate health education materials for Hispanic populations has been widely recognized, and Spanish-language materials are available through a number of private and governmental organizations. We convened two focus groups to elucidate preferences regarding how health-related messages are obtained and to identify which educational materials available in Spanish were preferred by 26 recently immigrated Hispanic homemakers who had received 15 different bimonthly written documents as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The group did like the telenovela content and felt that the video would be a good tool, not only for the clinic, but at health fairs and in school programs. The participants also stated that additional telenovelas or fotonovelas (story in print with pictures and captions) would be helpful in promoting other positive health behaviors, such as exercise and managing specific diseases, such as diabetes or asthma, which was consistent with the literature (Balcazar et al., ; Larson et al., ; Mier et al., ; Wilkin et al., ). Two areas for improvement according to the participants were to add more information about other healthy behaviors such as exercise, taking medications, etc., into the current storyline to enhance the content and to incorporate the use of community leaders or promotoras (LHA) to disseminate the information.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The group did like the telenovela content and felt that the video would be a good tool, not only for the clinic, but at health fairs and in school programs. The participants also stated that additional telenovelas or fotonovelas (story in print with pictures and captions) would be helpful in promoting other positive health behaviors, such as exercise and managing specific diseases, such as diabetes or asthma, which was consistent with the literature (Balcazar et al., ; Larson et al., ; Mier et al., ; Wilkin et al., ). Two areas for improvement according to the participants were to add more information about other healthy behaviors such as exercise, taking medications, etc., into the current storyline to enhance the content and to incorporate the use of community leaders or promotoras (LHA) to disseminate the information.…”
Section: Discussionsupporting
confidence: 78%
“…There is a myriad of health related education materials available in Spanish (in print and online). Materials developed by healthcare professionals often reflect what they perceive as important points and the element of cultural context is often missing (Larson, Wong‐McLoughlin, & Ferng, ). It was found that clear purposeful messaging was important, however, a preference for the delivery of information from family, friends, and neighbors was also cited as even more influential than print media.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason is evident: no training no practicum and no reminder service. Literature proved that the practical demonstration has positively influence the practices of an individual and their behavior at their work place [ 24 ]. Face to face trainings has been proven to be one of more effective strategies for improving the practices and health behavior, especially when combined with other training interventional approaches [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These interviews were also conducted during clinic hours, primarily when the patient was in the exam room to maintain privacy. We hypothesized that most patients had little or no experience with written health information based on previous reports in the literature describing similar populations (Larson, Wong-McLoughlin, & Ferng, 2009). The next step in developing our health information intervention included identifying appropriate topics based on two criteria: (a) content frequently covered in similar materials developed by federal agencies and nonprofit foundations for a more general Latino audience and (b) commonly seen diagnoses at the local clinic that serves the target audience.…”
Section: Methodsmentioning
confidence: 99%